(untitled) (Sunari Penjor : Journal of Anthropology, 2025)
Women working as laborers at Belantih Coffee Farm do not only carry out domestic roles but are also actively involved in plantation production. This indicates the dual burden they bear. This study aims to understand the roles of female laborers in Belantih Village and the factors influencing their involvement in the farm’s labor system. Using a social role theory based on gender and women’s empowerment framework, this research adopts an ethnographic method through observation, interviews, and literature review. The findings show that female laborers contribute to various stages of coffee production, from land preparation to online marketing. Their participation is influenced by sociocultural, economic, educational, resource-based, and internal policy factors. The active involvement of women enhances farm productivity and supports household economies.